Let m,n,z belong to N such that m and n divide z and gcd(m,n) = 1. Prove that m.n divides z.

To prove that m.n divides z, we need to show that z can be expressed as a product of m, n, and another natural number.

Given that m and n divide z, we can write:

z = a.m (for some natural number a)
z = b.n (for some natural number b)

To prove that m.n divides z, we need to find a natural number c such that z = c.(m.n).

Since gcd(m, n) = 1, m and n are coprime, which implies that there exist integers s and t such that:

1 = s.m + t.n

Multiplying both sides by z, we get:

z = s.m.z + t.n.z

Substituting the expressions for z in terms of m and n obtained earlier, we have:

z = s.(a.m).z + t.(b.n).z

Rearranging the equation, we get:

z = (s.a.z.m) + (t.b.z.n)

Now, let's define c = (s.a.z) = (t.b.z)

Therefore, we have:

z = c.(m.n)

Hence, we have shown that z can be expressed as a product of m, n, and the natural number c. This implies that m.n divides z, which completes the proof.